Gravidade do olho seco em pacientes internados em unidade de terapia intensiva: análise de conceito e construção de definições - Fernandes, Ana Paula Nunes de Lima (2015)
Dry eye syndrome is a multifactorial disease of the tear film, resulting from the instability of the lacrimal functional unit that produces volume change, up or tear distribution. In patients in intensive care the cause is enhanced due to various risk factors, such as mechanical ventilation, sedation, lagophthalmos, low temperatures, among others. The study's purpose is to build an assessment tool of Dry Eye Severity in patients in intensive care units based on the systematization of nursing care and their classification systems. The aim of this study is to build an assessment tool of Dry Eye Severity in hospitalized patients in Care Unit Intensiva.Trata is a methodological study conducted in three stages, namely: context analysis, concept analysis, construction of operational definitions and magnitudes of nursing outcome. For the first step we used the methodological framework for Hinds, Chaves and Cypress (1992). For the second step we used the model of Walker and Avant and an integrative review Whitemore seconds, Knalf (2005). This step enabled the identification of the concept of attributes, background and consequent ground and the construction of the settings for the result of nursing severity of dry eye. For the construction of settings and operational magnitudes, it was used Psicometria proposed by Pasquali (1999). As a result of context analysis, visualized from the reflection that the matter should be discussed and that nursing needs to pay attention to the problem of eye injury, so minimizing strategies are created this event with a high prevalence. With the integrative review were located from the crosses 19 853 titles, selected 215, and from the abstracts 96 articles were read in full. From reading 10 were excluded culminating in the sample of 86 articles that were used to analyze the concept and construction of settings. Selected articles were found in greater numbers in the Scopus database (55.82%), performed in the United States (39.53%), and published mainly in the last five years (48.82). Regarding the concept of analysis were identified as antecedents: age, lagophthalmos, environmental factors, medication use, systemic diseases, mechanical ventilation and ophthalmic surgery. As attributes: TBUT <10s, Schimer I test <5 mm in Schimer II test <10mm, reduced osmolarity. As consequential: the ocular surface damage, ocular discomfort, visual instability. The settings were built and added indicators such as: decreased blink mechanism and eyestrain.